(untitled) (Advances in Applied Mathematics and Mechanics, 2022)
This study is focused on the forest edge flow by using numerical method. To model the effects of a forest canopy on airflow, source terms are introduced into the governing equations. The lattice Boltzmann method in conjunction with the standard k−ε model is applied to solve the turbulent wind field. In order to perform the simulation on non-uniform grids, the Taylor series expansion and least square based lattice Boltzmann method (TLLBM) is adopted to improve the accuracy and computational efficiency. The present method and code are verified with an earlier forest edge simulation. A series of forest canopies are established to explore the impacts of canopy morphology on wind field. These canopies cover 3 canopy architectures and the Leaf Area Index (LAI) ranges from 2.0 to 4.0. The further study is carried out by adjusting the canopy foliage amount and the canopy architecture. The present study demonstrates the potential of lattice Boltzmann method to simulate the high Re number forest edge flow. The impacts of canopy morphology on zero plane displacement, aerodynamic roughness length, friction wind velocity, permeability coefficient, wall-shear stress are illustrated in detail. The results show that the canopy sub-layer wind field, especially the wind velocity profiles within and above the forest canopy, are mainly determined by canopy morphology.